Educator perspectives on mental health resources and practices in their school. Issue 11 (16th August 2021) - Ormiston, Heather E.; Nygaard, Malena A.; Heck, Olivia C.; Wood, Maureen; Rodriguez, Nicole; Maze, Mallory; Asomani‐Adem, Akua A.; Ingmire, Keelyn; Burgess, Bri; Shriberg, David
Abstract: The need for mental health services in schools is increasing. Teachers are expected to meet student's academic needs but may find their role impacted by the need for mental health support among students (Bruhn et al.,  2014; Kaffenberger & O'Rouke‐Trigiani,  2013). The purpose of this study is to elicit teacher perspectives on addressing the mental health needs of students in school. Staff members from one school in a Midwestern state were interviewed to examine their perspectives related to student mental health. Thirteen classroom teachers ( n  = 13), four related arts teachers ( n  = 4), seven special education staff members ( n  = 7), three building support personnel ( n  = 3), two office staff ( n  = 2), and four support staff members ( n  = 4) were interviewed, for a total of 33 participants ( n  = 33). Participant experience ranged from 2 to 37 years in education. Utilizing an inductive thematic analysis approach (Braun & Clarke,  2006), information regarding teachers' current knowledge of, roles, and approaches to support students with mental health needs in schools is presented across four main themes. Directions for future research, training, and practice are described.